2021
DOI: 10.1017/s1092852921000638
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of refractory obsessive–compulsive disorder with nutraceuticals (TRON): a 20-week, open label pilot study

Abstract: Background Obsessive–compulsive disorder (OCD) is often challenging to treat and resistant to psychological interventions and prescribed medications. The adjunctive use of nutraceuticals with potential neuromodulatory effects on underpinning pathways such as the glutamatergic and serotonergic systems is one novel approach. Objective To assess the effectiveness and safety of a purpose-formulated combination of nutraceuticals in treating OCD: N-acetyl cysteine, L-theanine, zinc, magnesium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…48,49 Additionally, in our recently completed open-label Treatment of Refractory Obsessive-Compulsive Disorder with Nutraceuticals (TRON) trial, we found that treatment response to a nutraceutical combination was substantially higher in participants with high levels of caffeine intake relative to those with low caffeine intake in a treatment resistant OCD sample. 26 It has been hypothesised that caffeine's modulation of tryptophan, serotonin and noradrenaline production via adenosine A1 and A2 receptor antagonism is also implicated in the pathophysiology of OCD. 49 However, larger samples and longer-term follow-up trials are required to determine whether a dose-response relationship exists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…48,49 Additionally, in our recently completed open-label Treatment of Refractory Obsessive-Compulsive Disorder with Nutraceuticals (TRON) trial, we found that treatment response to a nutraceutical combination was substantially higher in participants with high levels of caffeine intake relative to those with low caffeine intake in a treatment resistant OCD sample. 26 It has been hypothesised that caffeine's modulation of tryptophan, serotonin and noradrenaline production via adenosine A1 and A2 receptor antagonism is also implicated in the pathophysiology of OCD. 49 However, larger samples and longer-term follow-up trials are required to determine whether a dose-response relationship exists.…”
Section: Discussionmentioning
confidence: 99%
“…The second study (n = 28) was a 20-week, open-label pilot study that assessed the effectiveness and safety of a nutraceutical formulation for patients with treatment-resistant DSM-5-diagnosed OCD. 26 Participants were recruited at the same sites as the first study described above, between 2017 and 2020. Eligibility criteria included being aged 18-75 years, capacity as well as desire to consent to the study and follow its procedures, a primary DSM-5 diagnosis of moderate-to-extreme OCD (Y-BOCS ≥ 16), inadequate responses to at least three trials of serotonin reuptake inhibitors and at least one augmentation strategy as well as engagement in adequate OCD-specific cognitive-behavioural therapy.…”
Section: Study Overview Design and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a 20-week open label proof-of-concept study was undertaken involving 28 participants with pharmacologicalresistant OCD treated with a nutraceutical combination: N-acetyl cysteine, L-theanine, zinc, magnesium, pyridoxal-50 phosphate, and selenium. Statistically significant improvements were revealed on the YBOCS total score and secondary outcomes, suggesting the potential usefulness of this treatment option especially for patients with lower symptom levels [24].…”
Section: Discussionmentioning
confidence: 87%
“…Participants were randomly assigned into two groups using a simple randomization plan based on a random number list in a ratio of 1:1, the "N-group" (n = 17), which didn't receive the nutritional supplement for two months, and the "THE-group" (n = 17), which received the nutritional supplements L-Theanine (200 mg/day) and vitamin B6 (2.8 mg/day) for two months. Based on the previous clinical trials on neurodevelopmental disorders, dose selection for L-Theanine and vitamin B6 was considered safe and well tolerated to our patients [19,[21][22][23][24][25][26][27].…”
Section: Methodsmentioning
confidence: 99%